2015
DOI: 10.1589/jpts.27.1653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caregiver education on pulmonary rehabilitation, respiratory muscle strength and dyspnea in lung cancer patients

Abstract: [Purpose] This study evaluated the effects of caregiver education on pulmonary rehabilitation of patients who have undergone lung resection for cancer. [Subjects] Patients were divided into experimental (n = 22) and control (n = 19) groups. [Methods] The caregivers of the experimental group patients received education on pulmonary rehabilitation, while the control group patients received general management advice for 4 weeks. [Results] Pulmonary muscle strength (maximum inspiratory pressure and maximum expirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…More and more care models were proven to work for RA, and a nurse-led study found that nursing education by telephone was effective in improving medication adherence in RA patients[ 14 ]. As a rising approach, FCNE plays a positive role in the prognosis of diseases including lung cancer[ 24 ] and stroke[ 25 ]. FCNE enhances caregivers’ knowledge of the disease and improves nursing skills, which is conducive to providing better care to patients while identifying risk factors and complications in time to reduce injuries.…”
Section: Discussionmentioning
confidence: 99%
“…More and more care models were proven to work for RA, and a nurse-led study found that nursing education by telephone was effective in improving medication adherence in RA patients[ 14 ]. As a rising approach, FCNE plays a positive role in the prognosis of diseases including lung cancer[ 24 ] and stroke[ 25 ]. FCNE enhances caregivers’ knowledge of the disease and improves nursing skills, which is conducive to providing better care to patients while identifying risk factors and complications in time to reduce injuries.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the FMEP reduces cognitive impairment, anxiety, and depression in persons who have had a Home-based health care for persons who have had a stroke has been gradually gaining emphasis in recent years, due to the long-term care needs and to reduce high costs (Langhorne, Bernhardt, & Kwakkel, 2011). The FMEP has been identified as a useful method to promote understanding among family members or caregivers, resulting in better care for patients with various diseases, including Alzheimer's disease (AD), congenital heart disease, and pulmonary carcinoma (Goossens et al, 2015;Jeong & Yoo, 2015;Navab, Negarandeh, & Peyrovi, 2012;Watanabe, 2013). In line with these previous results, our study revealed that FMEP decreased cognitive impairment, as assessed by the MOCA score.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation education includes instruction on airway clearance techniques, splint cough, abdominal breathing, lip reduction breathing, upper and lower limb exercise, walking exercise, and stair exercise. In a randomized controlled experiment conducted by Jeong et al [31], pulmonary rehabilitation education was provided for patients in the experimental group and comprehensive management advice was provided for patients in the control group. After 4 weeks, respiratory muscle strength and dyspnoia of patients in the experimental group were signifi-cantly improved compared with those in the control group.…”
Section: Pulmonary Rehabilitation Educationmentioning
confidence: 99%